Pengaruh budaya kerja dan pembagian kerja terhadap kualitas pelayanan di Kecamatan Sumur Kabupaten Pandeglang - Dodi Rahmat Setiawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The aim of this study is to analyze the effect of work culture towards the quality of service, the effect of work division towards quality of service, and the effect of work culture and work division collectively towards the quality of service. The study used quantitative approach method; the population of this study is all people who use the service in Sumur District from October to December 2020 with total 134 people. The sample of this study is 134 people (saturated sample).Based on the result of the study, it can be concluded as follows: (1) there is positive and significant effect of work culture towards the quality of service in Sumur District, Pandeglang Regency for 29,9%. (2) there is positive and significant effect of work culture towards the quality of service in Sumur District, Pandeglang Regency for 30,7%. (3) there is positive and significant effect of work culture and work division collectively towards the quality of service in Sumur District, Pandeglang Regency for 59,9% and the rest is 40,1% that effected by other factors that are not studied.